In Vitro Evaluation of Essential Oils, Fractions and Terpenes against Clinical Isolates of Candida auris with Different Antifungal Susceptibility Profiles (2021)
ABSTRACT: Objectives: To evaluate in vitro essential oils, enriched fractions and terpenes against clinical isolates of C. auris with different antifungal susceptibility profiles. Materials & Methods: Four fluconazole-resistant C. glabrata isolates were used. FLZ-NLCs were prepared using the ultrasound technique. Each fluconazole-resistant C. glabrata isolate was exposed to fluconazole (alone and in the form of FLZ-NLCs) and placebo (NLCs without fluconazole (FLZ)) for 20 h at 37 ◦C and the total RNA extracted. Real-time PCRs were performed to assess the probable alternations in ATP-binding cassette transporter genes. Results: Under the FLZ-NLCs treated condition, no significant alteration was ob-served in the expression of CgCDR1, CgCDR2 and CgSNQ2 genes although the genes wereover-expressed when exposed to fluconazole. Conclusions: It is highly suggested that nanostructure lipid carrier may prevent drug detection by transporter’s proteins avoiding the drug pumping out. As such, the developed formulation may be fundamentally beneficial for the treatment of candidiasis caused by C. glabrata. Acknowledgments: The authors thank funding from the Ministry of Science, Tech-nology and Innovation, the Ministry of Education, the Ministry of Industry and Commerce.